2021
DOI: 10.3390/nu14010027
|View full text |Cite
|
Sign up to set email alerts
|

A Glimpse of the Sports Nutrition Awareness in Spanish Basketball Players

Abstract: Basketball is a team sport, with many fans and practitioners worldwide from all ages and levels. In all cases, players accumulate high levels of fatigue, and there is also limited time to recover between games or practices. In particular, nutrition plays a key role in optimizing performance and recovery. However, it is typical to observe erroneous nutritional behaviors among basketball players. It has been theorized that these behaviors are influenced by habits acquired based on the individual’s knowledge. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 88 publications
0
25
0
Order By: Relevance
“…), but the amount, type, timing and frequency of ingestion are critical concerns for sports nutrition [ 78 , 79 , 80 , 81 ] to prepare and recover athletes for the work required [ 18 ]. Basketball is a very demanding game with a short time to recover between games [ 4 ]; thus, having strong knowledge [ 26 ] about CHO fueling strategies may lead to a clear competitive advantage [ 5 ]. This review reaffirms CHO’s role in the recovery process [ 78 ], so when diet cannot cover these requirements, it may be recommendable support it with some ergogenic aids such as bars, gels, drinks, or similar until this recommendation is fulfilled.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…), but the amount, type, timing and frequency of ingestion are critical concerns for sports nutrition [ 78 , 79 , 80 , 81 ] to prepare and recover athletes for the work required [ 18 ]. Basketball is a very demanding game with a short time to recover between games [ 4 ]; thus, having strong knowledge [ 26 ] about CHO fueling strategies may lead to a clear competitive advantage [ 5 ]. This review reaffirms CHO’s role in the recovery process [ 78 ], so when diet cannot cover these requirements, it may be recommendable support it with some ergogenic aids such as bars, gels, drinks, or similar until this recommendation is fulfilled.…”
Section: Discussionmentioning
confidence: 99%
“…However, one important strength is that (to the best of our knowledge) this is the first systematic review describing which ergo-nutritional aids can be specifically useful in basketball to enhance on-court performance and recovery, boosting future studies and helping players and team staff to plan their ergo-nutritional aids wisely. This is critically important given that basketball players do not have enough nutritional knowledge to manage it on their own [ 26 ]. Thus, it should be noted that our systematic review should be taken as a first step to normalize study designs and categorize the main outcomes to get a big picture of the main effects of a nutritional supplementation intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining studies represented various sports, including track and field (47) , aesthetic sports (39) , endurance sports (34,35) and various team and individual sports (25)(26)(27)36,42,45,46) . Sporting levels included competitive (9,(21)(22)(23)26,30,32,34,35,39,40,42,49) , regional/state/national competitors (27)(28)(29)(36)(37)(38)43,47) , high school/college (19,24,27,33,41,45,57) , elite (20,44,46) and one study did not report sporting level (25) . NK was assessed using twenty-one questionnaires across thirty-two studies.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Three studies (34,35,38) using the Heikkila et al (58) questionnaire reported supplements to be the lowest scoring section. Likewise, Escribano-Ott et al (30) reported supplements as the lowest-scoring subsection, and Bird and Rushton (26) described the supplement section as the greatest source of uncertainty, with more 'don't know' responses than any other section (45 %). Similarly, two studies (26,30) that used questionnaires based on Zinn et al (59) reported poor scores.…”
Section: Yesmentioning
confidence: 99%